PENINGKATAN MUTU TK DAN PAUD DENGAN PENDAMPINGANGURU DAN ORANG TUA SISWA - Arif Wibowo (UII, 2013)
Early childhood education is an attempt to stimulate, guide, nurture and providelearning activities capable of generating abilities and skills of the child. Early childhoodeducation is an education conducted in children from birth to age eight. The process ofeducation and learning in early childhood should be done with the aim of providing ameaningful concept for children through a real experience. In early childhood childrenexperienced a golden age (the golden age) which is a period where the child startssensitive / insensitive to receive various stimuli. Sensitive period for each child isdifferent, along with the rate of growth and development of individual children. Sensitiveperiod is a period inwhich the physical and psychological maturity functions are ready torespond to the stimulation provided by the environment. This period is also the timethe foundation stone to develop cognitive abilities, motor, language, socio-emotional,religious and moral.